Inflexiones católicas y complicidades femeninas : sincretismos en un club de fans en Buenos Aires - Gallo, Guadalupe M; Spataro, Carolina (El Colegio de México, 2012)
The processes of appropriation of contemporary popular music, especially in massive genres and canonically undervalued, are not unknown. However, they host a rich variety of surprising ways that involve appropriation from openings of conscience to gender and social elaborations and resignifi cations from the religious. They all speak of the dense, but unknown symbolic plot, which ignores the ethnocentric rejection of mass culture.